Turner syndrome and postpubertal Empty sella syndrome: a case report and literature review - Lin, Fanyu; Zeng, Jing (Frontiers in Endocrinology, 2025)
IntroductionTurner syndrome is a common sex chromosome disorder characterized by short stature, gonadal dysgenesis, and hypergonadotropic hypogonadism. Empty Sella Syndrome is defined radiologically as the presence of cerebrospinal fluid filling the sella turcica and is associated with hypopituitarism. The association between TS and ESS is rare.MethodsWe present a case of Turner syndrome associated with Empty Sella Syndrome, characterized by complete development of secondary sexual characteristics but irregular menstruation. Magnetic resonance imaging of the pituitary gland revealed partial empty sella with evidence of pituitary compression. Laboratory investigations indicated hypogonadotropic hypogonadism, central hypothyroidism, and an insulin-induced hypoglycemia test suggested insufficient compensatory growth hormone secretion, while cortisol compensation was normal. To ascertain the correlation between Turner syndrome and Empty Sella Syndrome, we reviewed the literature and tried to explore the potential pathophysiological mechanisms underlying their co-occurrence, thereby providing evidence and reference value for clinical diagnosis.DiscussionThe etiology of post-pubertal pituitary dysfunction in patients with Turner syndrome remains obscure. Both primary and secondary Empty Sella Syndromes may be potential underlying causes, and some familial histories suggest the presence of an as-yet-undefined genetic-related patho-physiological mechanism that warrants further investigation.